PENERAPAN METODE RESITASI DENGAN MEDIA LKS UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KUBUS DAN BALOK KELAS VIII E SMP NEGERI 11 JEMBER TAHUN AJARAN 2013/2014 - Dewi, Ernita Sukarno; Hobri, Hobri; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2016)
This research is a research of class action. The purposes of this research are 1) to know about the motivation increasing from student to learn mathematic after learning applied using recitation method with LKS on standart topic on Cube and Beam in grade VIII E SMPN 11 Jember year 2013/2014; 2) To know result learning about the increasing from student to learn mathematic after learning applied using recitation method with LKS on standart topic on Cube and Beam in grade VIII E SMPN 11 Jember year 2013/2014. The research subject is students of SMPN 11 grade VIII. This research consists of 2 cycles. The data collecting method is observation, questionnaire, interview and test for every end of cycle. Based on the analysis result from the motivation questionnaire students in studying mathematic, the average from cycle value and interview about motivation increasing by the students to learn mathematic after using recitation method. The result is shown by 1) The data from questionnaire students in learning mathematic is getting increasing from the first reflection to the cycle I and to the cycle II is 57,15% becomes 69,87% and in cycle II becomes 76,5% with the high cathegory; The average from the test result is getting increasing, the average in cylce I is 68,37 becomes 81,13 in cycle II. The interview result is the students get a motivation to study generally. Based on the questionnaire result.